PERFORMANCE OF MANGROVE-FRIENDLY SEMI-CLOSED SHRIMP POND - Taufik Ahmad; Markus Mangampa; Muhammad Tjaronge (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
Mangrove has been ............